Individually adapted tube current selection and contrast medium injection protocol of coronary CT angiography based on test bolus parameters: a feasibility study. (June 2015) - Zhu, Xiaomei; Shi, Zhaofei; Zhu, Yinsu; Liu, Wangyan; Yang, Guanyu; Yu, Tongfu; Tang, Lijun; Xu, Yi
Background: Test bolus is mostly used to determine the starting point of a full cardiac scanning with respect to injection of a larger bolus of contrast material. So far there are limited data demonstrating the feasibility of using information obtained from a test bolus to adjust contrast delivery protocols and tube current individually during coronary computed tomography angiography (CCTA). Purpose: To evaluate the feasibility of individually adapted tube current selection and contrast injection protocols of CCTA based on test bolus parameters. Material and Methods: Test bolus followed by CCTA was performed in 93 patients at 100 kV and in 81 patients at 120 kV, respectively. Simulated attenuation of the descending aorta (SimDA ) of CCTA was calculated at a fixed contrast injection rate of 4 mL/s. Univariate and multivariate comparisons were performed to identify associations of SimDA and image noise of CCTA (NoiseCCTA ) with test bolus information and patient-related factors including body weight (BW), body mass index (BMI), and body surface area (BSA). Results: Compared with BW, BMI, and BSA, SimDA was more closely related to the peak time of left ventricle and peak enhancement of right ventricle obtained from test bolus ( r  = 0.495 and r  = 0.642 for 100 and 120 kV protocol, respectively). Similarly, NoiseTB was much more closely related to NoiseCCTA ( r  = 0.740 and r  = 0.630 for 100 and 120 kV protocol, respectively) when compared with BW, BMI, and BSA. Conclusion: It is feasible to individually adapt tube current and contrast injection protocol of CCTA based on the information of test bolus.